2013
DOI: 10.1186/1471-244x-13-143
|View full text |Cite
|
Sign up to set email alerts
|

A long-term, phase 2, multicenter, randomized, open-label, comparative safety study of pomaglumetad methionil (LY2140023 monohydrate) versus atypical antipsychotic standard of care in patients with schizophrenia

Abstract: BackgroundWe compared the time to discontinuation due to lack of tolerability over 24 weeks in patients suffering from schizophrenia treated with pomaglumetad methionil (LY2140023 monohydrate, the prodrug of metabotropic glutamate 2/3 receptor agonist, LY404039) or standard of care (SOC: olanzapine, risperidone, or aripiprazole).MethodsStudy HBBR was a multicenter, randomized, open-label study comparing the long-term safety and tolerability of LY2140023 with SOC for schizophrenia. Patients had moderate symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
95
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 9 publications
(13 reference statements)
1
95
0
Order By: Relevance
“…This receptor, a class C GPCR, has emerged as therapeutic target for various psychiatric diseases amongst which schizophrenia, depression and anxiety, which are characterized by glutamatergic dysfunction [10,11]. A variety of glutamate-like agonists that can dampen glutamate hyperfunction was developed, of which LY2140023 of Eli Lilly, a prodrug of LY404039 showed improvement in positive and negative symptoms in schizophrenic patients, which could not be confirmed in later clinical studies [12,13]. Inhibition of the mGlu 2 receptor can be beneficial for glutamate hypofunction in depression, and when considering the orthosteric binding site antagonist LY341495 has been the most studied for this purpose [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This receptor, a class C GPCR, has emerged as therapeutic target for various psychiatric diseases amongst which schizophrenia, depression and anxiety, which are characterized by glutamatergic dysfunction [10,11]. A variety of glutamate-like agonists that can dampen glutamate hyperfunction was developed, of which LY2140023 of Eli Lilly, a prodrug of LY404039 showed improvement in positive and negative symptoms in schizophrenic patients, which could not be confirmed in later clinical studies [12,13]. Inhibition of the mGlu 2 receptor can be beneficial for glutamate hypofunction in depression, and when considering the orthosteric binding site antagonist LY341495 has been the most studied for this purpose [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Although no selective agonists exist, several nonselective mGluR agonists have entered late-stage clinical trials (Patil et al, 2007;Adams et al, 2013), but none has successfully reached the market. These clinical setbacks may be attributed to the lack of subtype selectivity, as studies suggest that even within groups, individual mGluR can play opposing physiological roles (Conn and Pin, 1997;Caraci et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is preclinical evidence to suggest that fenobam (an mGluR5 negative allosteric modulator) may effectively treat cocaine addiction (Keck et al, 2013), and fenobam has shown promising results in an open-label trial for fragile X (Berry-Kravis et al, 2009). LY404039 [(2)-(1R,4S,5S,6S)-4-amino-2-sulfonylbicyclo[3.1.0]hexane-4,6-dicarboxylic acid] is an mGluR2/3 agonist that partly attenuates an animal model of alcohol addiction (Rodd et al, 2006) and has been investigated in a phase 2 trial for schizophrenia (Adams et al, 2013). It remains to be seen whether trials of drugs targeting mGluRs for treating addiction will be successful.…”
mentioning
confidence: 99%